Sweet gourd production under sandbar cropping practices: a case study in Sundorganj of Gaibandha District in Bangladesh (Progressive Agriculture, 2016)
The present study analyzed the profitability of sweet gourd production under Sandbar Cropping Practice (SCP) and its impact on livelihood improvement of the farmers in Sundorgonj of Gaibandha district in Bangladesh. A total of 60 sweet gourd farmers were selected using stratified random sampling technique. Evidence showed that sweet gourd production under SCP was highly profitable and had a positive impact on livelihood improvement of farmers. Per hectare gross return of sweet gourd production for all sampled farmers was BDT 230506 and the net return was BDT 136391. The net return was the highest for small farmers and this was the lowest for large farmers. It was found that all kinds of livelihood assets of sampled farmers increased due to sweet gourd production under SCP. The availability of high quality HYV seeds was required to sustain sweet gourd production. The labour saving technology affordable by the farmers is suggested in addition to appropriate training facilities and sufficient extension services for the betterment of farmers.Progressive Agriculture 27 (3): 320-326, 2016